2022
DOI: 10.1002/mpr.1910
|View full text |Cite
|
Sign up to set email alerts
|

Sample size and precision of estimates in studies of depression screening tool accuracy: A meta‐research review of studies published in 2018–2021

Abstract: Objectives Depression screening tool accuracy studies should be conducted with large enough sample sizes to generate precise accuracy estimates. We assessed the proportion of recently published depression screening tool diagnostic accuracy studies that reported sample size calculations; the proportion that provided confidence intervals (CIs); and precision, based on the width and lower bounds of 95% CIs for sensitivity and specificity. In addition, we assessed whether these results have improved since a previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…However, we found that 72% of included studies did not specify the targeted sample size including how it was calculated. Similar trends were observed in reviews of depression screening tool accuracy studies published between (1) and 36 (34%) provided reasonably accurate confidence intervals (Nassar et al, 2022a). Importantly, accuracy studies with small samples sizes often fail to identify the most accurate cut-off and overstate accuracy estimates for the cut-offs they report (Bhandari et al, 2021).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…However, we found that 72% of included studies did not specify the targeted sample size including how it was calculated. Similar trends were observed in reviews of depression screening tool accuracy studies published between (1) and 36 (34%) provided reasonably accurate confidence intervals (Nassar et al, 2022a). Importantly, accuracy studies with small samples sizes often fail to identify the most accurate cut-off and overstate accuracy estimates for the cut-offs they report (Bhandari et al, 2021).…”
Section: Discussionsupporting
confidence: 66%
“…However, we found that 72% of included studies did not specify the targeted sample size including how it was calculated. Similar trends were observed in reviews of depression screening tool accuracy studies published between (1) 2013 and 2015, where only three of 89 (3%) studies described a viable sample size calculation and 30 studies (34%) provided reasonably accurate confidence intervals around accuracy estimates (Thombs & Rice, 2016 ) and (2) 2018 and 2021, where only 12 of 106 (11%) studies described a viable sample size calculation and 36 (34%) provided reasonably accurate confidence intervals (Nassar et al., 2022a ). Importantly, accuracy studies with small samples sizes often fail to identify the most accurate cut‐off and overstate accuracy estimates for the cut‐offs they report (Bhandari et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any decision analysis to select cutoffs for use in future trials should rely upon evidence from large, high-quality meta-analyses. (Nassar et al, 2022). Furthermore, two-step methods, in which all participants with positive screens but only a proportion with negative screens are assessed with diagnostic interviews, could be used to obtain satisfactory precision for both sensitivity and specificity (Thombs et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…If optimal cutoffs are identified, possible bias from data‐driven methods and imprecision of estimates should be noted, and these factors should be considered before author recommendations are made. As recommended by STARD, a priori sample size calculations should be conducted in depression screening tool accuracy studies to avoid drawing potentially misleading conclusions from overly small samples, but only approximately 10% of such studies report sample size calculations (Nassar et al., 2022). Furthermore, two‐step methods, in which all participants with positive screens but only a proportion with negative screens are assessed with diagnostic interviews, could be used to obtain satisfactory precision for both sensitivity and specificity (Thombs et al., 2018).…”
Section: Discussionmentioning
confidence: 99%